Effects of harvest month on biochemical composition of alligator weed for biohydrogen and biomethane cogeneration：Identifying critical variations in microbial communities. (7th February 2020) - Li, Hui; Song, Wenlu; Cheng, Jun; Ding, Lingkan; Zhou, Junhu; Li, Yu-You
Abstract: To determine the optimal harvest period for alligator weed used in fermentation-based gaseous biofuel production, the effects of harvest months on the biochemical composition and fermentative hydrogen and methane co-production from alligator weed were evaluated. Compositional analysis indicates that alligator weed harvested in September was most suitable for fermentative hydrogen production because it exhibited an appropriate carbon to nitrogen molar ratio (26.75), the highest cellulose content (20.34%) and the lowest weight ratio of ash to volatiles (0.09). Biohydrogen production was significantly affected by the harvest month, peaking at 48.4 mL/g VS in September. Microbial community analysis suggests that the abundance of Clostridium sensu stricto, the dominating hydrogen producer in dark fermentation reactors, was greatly enriched with feedstock harvested in September. Moreover, the expression levels of functional genes involved in carbohydrate metabolism and microbial proliferation were highest in the reactor fed with feedstock harvested in September. During the second-stage anaerobic digestion (AD), biomethane yield mainly depended on the soluble COD content in the hydrogenogenic effluent and was highest in August (214.6 mL/g VS). A maximum total energy conversion efficiency of 44.8% was obtained in September through two-stage process combining dark fermentation and AD. Highlights: Optimal C/N ratio and highest cellulose content (20.34%) were obtained in Sep. Biohydrogen yield (~48.4 mL/g VS) from alligator weed was highest in Sep. Clostridium sensu stricto were greatly enriched with feedstock harvested in Sep. Biomethane yield (~214.6 mL/g VS) from hydrogenogenic effluent peaked in Aug. Total energy conversion efficiency peaked in Sep. via two-stage fermentation.